2022
DOI: 10.31470/2309-1797-2022-31-1-118-140
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Analysis of the Students’ Experience with Digital Media in L2 Acquisition

Abstract: Aim. Foreign language education widely utilizes various forms of eLearning or blended learning techniques and tools, and this trend has recently been supported and speeded up by the global pandemics of COVID-19. The study attempts to analyse the students’ experience with the use of digital media used for foreign language education with the aim of providing clear implications needed for future digital (online) language higher education. Methodology. The methodology used to collect data was a questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The other competency, which was chosen by the respondents, is pedagogical. The pedagogical roles of online teachers are to design and prepare instructional strategies for the students, develop and use appropriate learning resources, use instructional methods in teaching, encourage participation among students, work on increasing students' motivation and work on facilitating the study material (Pikhart et al, 2022). All these roles are essential according to the respondents' answers.…”
Section: Discussionmentioning
confidence: 99%
“…The other competency, which was chosen by the respondents, is pedagogical. The pedagogical roles of online teachers are to design and prepare instructional strategies for the students, develop and use appropriate learning resources, use instructional methods in teaching, encourage participation among students, work on increasing students' motivation and work on facilitating the study material (Pikhart et al, 2022). All these roles are essential according to the respondents' answers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Çakmak et al ( 2021 ) reported the essential role of online education, specifically in vocabulary learning and retention. On the contrary, Pikhart et al ( 2022 ) found some dissatisfaction among students with online education in the EFL context as they much prefer traditional face-to-face classes and written textbooks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that teachers thought students needed more instruction in using learning management systems, they did not take online instruction seriously, and that emergency remote teaching increased cheating among students. Another important point was hit by Pikhart, Al-Obaydi, and Abdur Rehman [ 20 ] who claim students typically use their computers and/or smartphones for a variety of activities, including social media, communication, gaming, and many others, but none of these activities has a set amount of time allotted for them which only led to an increased screen-time without any significant benefit for the students. So, there was serious discontent among the students as a result of their excessive time in front of screens, which seems as a crucial issue that must be taken into consideration very seriously but previous research ignored this topic whatsoever.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As part of the potential pitfalls of online teaching, many problems and challenges, in relation to students’ performance and online class environment in online education, were mentioned repeatedly by some authors, such as the lack of communication channels between teachers and students [ 14 , 15 ], little or no group work or social tasks [ 16 , 17 ], increasing the loads on students such as homework and different online activities and tasks [ 18 ], the lack of humanistic learning elements [ 19 ], related health and psychological problems [ 7 ], long time of screen exposure [ 17 , 20 ], negative effects on speaking skill [ 21 ], encouraging cheating among students [ 9 ], how to deal with critical pedagogy aspects [ 22 ], and finally, low technological literacy of students or even teachers [ 23 ]. The total image of how many issues there are related to the online FLL are not clear yet since not much light is shed on the topic.…”
Section: Introductionmentioning
confidence: 99%